التسجيلات المحاسبية للفروع والمجمعات وفق النظام المحاسبي المالي دراسة حالة مجمع المؤسسة الوطنية للخدمات في الآبار ENSP - زيدان, يوسف (University of eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى معرفة كيفية المعالجة المحاسبية للفروع والمجمعات انطلاقا من تزايد عدد المؤسسات الاقتصادية المنظمة في شكل مجمعات، مع أن هذه الدراسة قد مكنتنا من الوقوف على الجانب التقني المتمثل في التسجيلات المحاسبية بين المجمع وفروعه، وعرض القوائم المالية المجمعة عوضا عن القوائم المالية الفردية للشركة الأم في تلبية حاجيات المساهمين والمستثمرين فيها أصبح ضرورة تمليه حاجة المسيرين من جهة و المبادئ المنظمة لمهنة المحاسبة من جهة أخرى. بعد إستعراض مختلف الجوانب النظرية والمتعلقة بسيرورة التجميع وطرق الإدماج والمعالجة المحاسبية للفروع والمجمعات، جاءت الدراسة العملية من خلال إختيارنا لمجمع جزائري وذلك لإثبات مدى تحكمه في أسس وقواعد التجميع وصولا إلى عرض القوائم المالية المجمعة. أظهرت نتائج الدراسة تحكم المؤسسة محل الدراسة في قواعد التجميع ومنه إعطاء صورة صادقة للقوائمالمالية. This study aims at understanding the accounting treatment of branches and complexes based on the increasing number of organized economic institutions in the form of complexes, although this study has enabled us to identify the technical aspect of the accounting records between the complex and its branches and to present the consolidated financial statements instead of the individual financial statements of the company The mother in meeting the needs of shareholders and investors has become a necessity dictated by the need of managers on the one hand and the principles governing the profession of accounting on the other. After reviewing the various theoretical aspects related to the process of consolidation and the methods of integration and accounting treatment of branches and complexes, the study came through the selection of an Algerian compound to prove its control over the bases and rules of compilation and to present the consolidated financial statements. The results of the study showed that the institution in question is governed by the rules of aggregation, which gives a true picture of the financial statements
مذكرة ماستر محاسبة
Keywords: التجميع،المجمع،القوائم المالية المجمعة.; Collection, Compound, Consolidated Financial Statements